Development and Climate Change in OIC Countries: Examining Causality between Economic Development, Energy Consumption, and Emissions - Irfany, Mohammad Iqbal; Tarmizi, Muhamad Mulya; Fitri, Resfa; Hasanah, Neneng (International Journal of Energy Economics and Policy, 2022)
OIC countries experience a fast and stable socio-economic development over the last decades. However, in the same time environmental degradation have also escalated as a consequence of its development. A central question raises whether OIC countries can push socio-economic growth without reducing environmental quality, or whether this region can implement emission reduction strategies without impeding their growth potentials. In this regards, this study examines the econometric relationships between emissions and socio-economic including output, population, emission intensity, investment, and urbanization. Employing panel data from 49 OIC countries from 1990 to 2019, the results show that GDP per capita, population, emission intensity, value-added industries, and proportions of urban communities significantly affect per capita CO2 emissions. It is suggested that climate change mitigation in emissions by OIC countries needs to be carried out both in the short and long term in reducing their dependence on fossil energy use both in production and consumption side, including the environmentally friendly technologies.